2019
DOI: 10.1016/j.physbeh.2019.112562
|View full text |Cite
|
Sign up to set email alerts
|

The scent of the other women: Body odor-induced behavioral and physiological effects on face categorization

Abstract: In body odor research, the interaction of female donors and receivers is scarcely investigated. With the aim to investigate effects of female body odor in a competitive context, we tested 51 women divided into two groups (i.e., a competitive and a non-competitive group, based on verbal instructions). Between groups, we explored whether female body odor exposure (vs. masker odor) modulates emotion categorization (via RT variance and distribution) and physiological reactions (via instantaneous heart rate) in a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…These results therefore suggest that those components of BO that are associated with anxiety induce a stress response in recipients, modulating both their arousal and cognitive-emotional skills but at the same time facilitating the processing of emotional facial stimuli (cf. Mutic et al, 2019 ). The presence of a fear odour facilitates the detection of fearful expressions over other negative expressions (Kamiloglu et al, 2018 ; cf.…”
Section: The Influence Of a Person’s Natural Body Odour On Multisensory Person Perceptionmentioning
confidence: 99%
“…These results therefore suggest that those components of BO that are associated with anxiety induce a stress response in recipients, modulating both their arousal and cognitive-emotional skills but at the same time facilitating the processing of emotional facial stimuli (cf. Mutic et al, 2019 ). The presence of a fear odour facilitates the detection of fearful expressions over other negative expressions (Kamiloglu et al, 2018 ; cf.…”
Section: The Influence Of a Person’s Natural Body Odour On Multisensory Person Perceptionmentioning
confidence: 99%
“…Furthermore, it has been showed that female body odour modulates male and female face emotion categorization in women 16 . While, Syrjänen et al 17 demonstrated that contextual background odours can modulate emotion and the N 170 cortical event‐related potential (ERP) responses of participants in faces pictures perception.…”
Section: Introductionmentioning
confidence: 99%
“…For example, compared to a "no scent" condition, exposure to lavender scent can increase interpersonal trust, as measured by the amount of money one participant (the trustor) transfers to another participant (the trustee) during the "Trust Game" [38]. Body odors and fragrances worn by one another have also been found to modulate interpersonal behaviors and social communications [39][40][41]. Baron [39] showed that job applicants wearing a pleasant perfume or cologne received significantly different performance reviews compared to a no-scent control.…”
Section: Introductionmentioning
confidence: 99%